Pelanggaran Hukum Hak Atas Merek dalam Hubungannya dengan Persaingan Usaha Tidak Sehat di Indonesia - Ni Made Ratih Prameswari; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Fakultas Hukum Universitas Warmadewa, 2021)
The number of brand violations that can be categorized as unfair business competition, which still produces counterfeit products and persists to this day because the public's interest in brand products is still very large because prices are much more expensive. This study aims to find out what forms of violation of trademark rights are categorized as unfair business competition and what legal remedies are available for business actors who market brands without permit. This study uses a normative legal research method by making legal norms the object of the research. The results of the study stated that the violation of trademark rights was categorized as unfair business competition, which was concluded through imitation of the brand, in essence, such as installing a logo exactly with the original brand that was already well-known. As for legal remedies for business actors who market brands without a permit, they can be subject to sanctions, in article 382bis of the Criminal Code, sanctions can also be imposed, namely material acts that are punishable by maximum imprisonment of 1 year and maximum fine of Rp.900,000,000.00.